A composite membrane of NH2-MIL-101(Fe) / bacterial cellulose, its preparation method and application
Patent Information
- Application Number
- CN202611368351.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-23
AI Technical Summary
[0007]本发明针对现有技术中粉体MOFs回收困难、MOF/BC复合膜中MOF负载不均匀、界面结合力弱、制备工艺复杂等技术问题,提供了一种NH2-MIL-101(Fe)/细菌纤维素复合膜及其制备方法和应用
(1)本发明通过TEMPO氧化处理在细菌纤维素纳米纤维表面引入丰富的羧基官能团,利用羧基与MOF前驱体中铁离子的配位作用,为NH2-MIL-101(Fe)的原位生长提供了大量均匀分布的成核锚定位点。通过SEM观察可知,NH2-MIL-101(Fe)颗粒沿BC纳米纤维脉络有序生长、均匀分布,无显著团聚,复合膜保持了BC的三维多孔网络结构。FTIR和XPS分析证实了MOF与BC之间形成了酰胺键共价键合,实现了MOF颗粒的牢固负载,有效解决了粉体MOFs易团聚、难回收以及物理混合法中MOF易脱落的问题。
Smart Images

Figure CN122955472A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomaterials and water treatment technology, specifically to an NH2-MIL-101(Fe) / bacterial cellulose composite membrane, its preparation method, and its application. Background Technology
[0002] Water pollution is one of the major environmental problems facing the world today. With the acceleration of industrialization and urbanization, large amounts of synthetic dyes, antibiotics, and other organic pollutants are discharged into natural water bodies, posing a serious threat to aquatic ecosystems and human health. Synthetic dyes are structurally stable and difficult to biodegrade; even at extremely low concentrations, they can severely impact aquatic landscapes and the ecological environment. Antibiotic residues can induce bacterial resistance, disrupt ecological balance, and pose potential risks to human health. Adsorption technology has received widespread attention in the field of advanced wastewater treatment due to its advantages such as ease of operation, high treatment efficiency, and wide applicability. The selection of adsorption materials is crucial in determining adsorption performance.
[0003] Metal-organic frameworks (MOFs) are a class of porous materials formed by the self-assembly of metal ions and organic ligands. They possess advantages such as large specific surface area, high porosity, and tunable pore structure, exhibiting excellent adsorption performance for pollutants such as dyes and antibiotics in water. Among them, iron-based MOFs have attracted much attention due to the abundance of iron resources and their environmental friendliness. In particular, amino-functionalized MIL-101(Fe) (i.e., NH2-MIL-101(Fe)) has improved adsorption performance by increasing the density of active sites and enhancing electrostatic interactions with negatively charged pollutants due to the introduction of amino groups (-NH2). However, traditional powdered MOFs suffer from problems such as easy agglomeration, difficulty in solid-liquid separation, and difficulty in recycling and reuse in practical applications, which seriously restricts their large-scale engineering applications.
[0004] Bacterial cellulose (BC) is a natural polymer synthesized by microorganisms, possessing high purity, a three-dimensional nanofiber network structure, excellent mechanical strength, and good biocompatibility and biodegradability. The surface of BC is rich in hydroxyl functional groups, making it an ideal carrier for functional materials. Loading MOFs onto the BC three-dimensional nanofiber network to prepare composite membrane materials not only leverages the high adsorption performance of MOFs but also utilizes the BC carrier to achieve integrated material forming and convenient recycling, representing an effective strategy to overcome the bottlenecks in the application of powdered MOFs.
[0005] In recent years, researchers have conducted a series of studies on the preparation of MOF / cellulose composites. Reference 1 (Facile preparation of nanocellulose / Zn-MOF-based catalytic filter for waterpurification by oxidation process, WK Zhu et al. Environmental Research 205(2022)112417) reported the preparation of ZIF-8 / cellulose nanofiber catalytic filter membrane by physical mixing and vacuum filtration. However, in this method, the binding between MOF and cellulose mainly relies on hydrogen bonding and electrostatic interaction, resulting in weak binding force. During long-term use, MOF particles are prone to detachment, affecting the stability and reusability of the material. Reference 2 (Oriented 2D metalorganic framework coating on bacterial cellulose for nitrobenzene removal from water by filtration, XY Yin et al. Separation and Purification Technology 276(2021)119366) uses hyaluronic acid to functionalize BC and then grows Cu(BDC) MOF coating in situ. However, this method involves a complex surface modification process, which is cumbersome and only applicable to specific 2D MOF systems, thus limiting its versatility.
[0006] In summary, existing MOF / BC composite membrane materials still have the following technical problems: (1) uneven MOF loading, easy particle agglomeration, affecting the exposure of effective adsorption sites; (2) weak bonding between MOF and BC substrate, easy detachment during use, and poor material stability; (3) complex preparation process, involving multiple steps of surface modification or post-treatment, high cost, and poor universality; (4) insufficient controllability of membrane structure, making it difficult to balance MOF loading with the mechanical properties and mass transfer efficiency of the composite membrane. Therefore, developing a MOF / BC composite membrane material with uniform MOF loading, strong interfacial bonding, controllable structure, simple preparation, and easy recycling is of great significance for promoting the practical application of high-performance adsorption materials in water pollution control. Summary of the Invention
[0007] This invention addresses the technical problems in existing technologies, such as the difficulty in recovering powdered MOFs, uneven MOF loading in MOF / BC composite membranes, weak interfacial bonding, and complex preparation processes. It provides an NH2-MIL-101(Fe) / bacterial cellulose composite membrane, its preparation method, and its applications. This invention utilizes the abundant oxygen-containing functional groups on the surface of bacterial cellulose oxidized by TEMPO as nucleation anchors, combined with an in-situ hydrothermal growth method to achieve uniform and robust loading of NH2-MIL-101(Fe) in the three-dimensional nanofiber network of bacterial cellulose. The resulting composite membrane has a controllable structure, good stability, and excellent adsorption performance for aquatic pollutants such as organic dyes and antibiotics. Furthermore, it is easily recovered and reused as a whole.
[0008] The technical solution adopted by this invention to solve the above-mentioned technical problems is as follows: Utilizing the abundant carboxyl and hydroxyl functional groups on the surface of TEMPO-oxidized bacterial cellulose nanofibers as nucleation anchoring sites, during a simultaneous hydrothermal reaction, an iron source and 2-aminoterephthalic acid ligand are grown in situ on the surface of BC nanofibers to form NH2-MIL-101(Fe) crystals, thus achieving a composite membrane with a hierarchical porous structure and tightly interwoven MOF particles and cellulose fibers. This composite membrane combines the high specific surface area and abundant amino active sites of NH2-MIL-101(Fe) with the excellent mechanical strength, three-dimensional network structure, and convenient recyclability of bacterial cellulose membranes, and can be used as a highly efficient adsorbent material for the removal of pollutants from water bodies.
[0009] A method for preparing an NH2-MIL-101(Fe) / bacterial cellulose composite membrane includes the following steps: (1) After the bacterial cellulose raw material is oxidized by the TEMPO oxidation system, it is then homogenized to obtain a TEMPO oxidized bacterial cellulose nanofiber suspension. (2) Iron salt and 2-aminoterephthalic acid were dissolved in an organic solvent to prepare a precursor solution; (3) The TEMPO-oxidized bacterial cellulose nanofiber suspension was mixed with the precursor solution and an in-situ growth reaction was carried out under hydrothermal conditions to load NH2-MIL-101(Fe) crystals on bacterial cellulose nanofibers in situ, thereby obtaining NH2-MIL-101(Fe) / bacterial cellulose composite material. (4) After washing the composite material to remove unreacted substances, it is subjected to film formation treatment and dried to obtain NH2-MIL-101(Fe) / bacterial cellulose composite membrane.
[0010] Further, in step (1), the TEMPO oxidation system contains 4-acetamido-TEMPO, NaClO, and NaClO2. In this system, NaClO acts as the main oxidant to oxidize the primary alcohol hydroxyl group to an aldehyde group, and NaClO2 further oxidizes the aldehyde group to a carboxyl group, thereby increasing the carboxyl content on the cellulose surface and providing abundant nucleation anchoring sites for the subsequent in-situ growth of MOFs. The reaction temperature for the oxidation treatment is 50–70°C, and the reaction time is 12–36 h; preferably, the reaction temperature is 60°C, and the reaction time is 24 h.
[0011] Further, in step (1), the bacterial cellulose raw material is a bacterial cellulose hydrogel, and the oxidation reaction is carried out in a phosphate buffer solution. The phosphate buffer solution is a NaH2PO4-Na2HPO4 buffer system with a concentration of 0.01-0.1M and a pH of 5.5-6.5. Preferably, the concentration is 0.05M and the pH is 6.0.
[0012] Further, in step (1), the homogenization process is a gradient homogenization process, first homogenizing at 6000-10000 rpm for 3-10 min, and then homogenizing at 8000-12000 rpm for 3-10 min. Preferably, homogenizing at 8000 rpm for 5 min is repeated twice; then homogenizing at 10000 rpm for 5 min is repeated twice.
[0013] Further, in step (2), the iron salt is ferric chloride hexahydrate (FeCl3·6H2O), and the molar ratio of the iron salt to 2-aminoterephthalic acid is 1:1 to 3:1. Preferably, the molar ratio of the iron salt to 2-aminoterephthalic acid is 2:1.
[0014] Further, in step (2), the organic solvent is N,N-dimethylformamide (DMF).
[0015] Further, in step (3), the volume ratio of the TEMPO-oxidizing bacterial cellulose nanofiber suspension to the precursor solution is 1:2 to 2:1; Further, in step (3), the hydrothermal reaction conditions are: reaction temperature 100-150℃, reaction time 20-30h. Preferably, the reaction temperature is 110℃ and the reaction time is 24h.
[0016] Further, in step (4), the washing includes: first, centrifugation washing with ethanol, then activation treatment with hot ethanol, and finally centrifugation washing with deionized water. Specifically, first, centrifugation washing with ethanol at 6000-10000 rpm three times, each time for 5-15 min; then activation with hot ethanol at 50-70℃ once for 1-5 h; finally, centrifugation washing with deionized water at 6000-10000 rpm three times, each time for 5-15 min. Preferably, the washing conditions are: centrifugation washing with ethanol at 8000 rpm three times, each time for 10 min; activation with hot ethanol at 60℃ for 3 h; and centrifugation washing with deionized water at 8000 rpm three times, each time for 10 min.
[0017] Furthermore, in step (4), the film-forming process is vacuum filtration film formation.
[0018] Further, in step (4), the drying process is either vacuum oven drying or freeze drying. The vacuum oven drying temperature is 40–80°C, and the drying time is 12–48 hours; the freeze drying involves first pre-freezing the composite membrane at -20–-80°C for 6–24 hours, and then transferring it to a freeze dryer for 12–48 hours. Preferably, the drying method is freeze drying, specifically: pre-freezing the composite membrane in a -20°C refrigerator for 12 hours, and then transferring it to a freeze dryer for 24 hours. The composite membrane obtained by freeze drying has a smooth surface, good flexibility, and a more obvious porous structure and higher porosity.
[0019] The present invention also provides an NH2-MIL-101(Fe) / bacterial cellulose composite membrane, which is prepared by the above preparation method.
[0020] In the composite membrane, NH2-MIL-101(Fe) particles are uniformly distributed along the three-dimensional nanofiber network of bacterial cellulose, without significant aggregation. The MOF loading can be controlled by adjusting the precursor concentration and reaction conditions. When freeze-dried, the composite membrane maintains its complete BC three-dimensional network structure, with a specific surface area reaching 46.8–119.2 m². 2 / g, with a pore size distribution of approximately 0.8 nm. Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) analyses confirmed the existence of a chemical bond between NH2-MIL-101(Fe) and TEMPO-BC, with a wavelength of 1651 cm⁻¹. -1 The presence of a characteristic absorption peak for amide bonds indicates that the two are firmly bonded by covalent bonds.
[0021] The present invention also provides the application of the above-mentioned NH2-MIL-101(Fe) / bacterial cellulose composite membrane, wherein the NH2-MIL-101(Fe) / bacterial cellulose composite membrane is used to adsorb organic pollutants in water, wherein the organic pollutants are selected from at least one of organic dyes and antibiotics. Preferably, the composite membrane is used to adsorb methylene blue and / or tetracycline in water.
[0022] Adsorption experiments showed that the composite membrane's adsorption of methylene blue better conformed to the Langmuir isotherm model, with a theoretical maximum adsorption capacity of 297.96 mg / g; its adsorption of tetracycline better conformed to the Freundlich isotherm model, with a theoretical maximum adsorption capacity of 314.38 mg / g. After five cycles of use, the composite membrane maintained a removal rate of over 85% for organic pollutants.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention introduces abundant carboxyl functional groups on the surface of bacterial cellulose nanofibers through TEMPO oxidation treatment. Utilizing the coordination of carboxyl groups with iron ions in the MOF precursor, a large number of uniformly distributed nucleation anchoring sites are provided for the in-situ growth of NH2-MIL-101(Fe). SEM observation shows that NH2-MIL-101(Fe) particles grow orderly and uniformly distributed along the BC nanofiber network without significant agglomeration, and the composite membrane maintains the three-dimensional porous network structure of BC. FTIR and XPS analyses confirm that amide covalent bonds are formed between MOF and BC, achieving a robust loading of MOF particles and effectively solving the problems of easy agglomeration and difficult recovery of powdered MOFs, as well as the easy detachment of MOFs in physical mixing methods.
[0024] (2) This invention enables controllable adjustment of MOF loading and composite membrane pore structure by regulating reaction temperature, time, precursor ratio, and drying method. Optimization of precursor usage achieves an optimal balance between MOF loading and composite membrane structural integrity. By selecting vacuum oven drying or freeze-drying methods, the structural density and porosity of the composite membrane can be further controlled, achieving a specific surface area of up to 119.2 m². 2 / g, achieving targeted optimization of adsorption performance.
[0025] (3) The composite membrane obtained in this invention exhibits excellent adsorption performance for both methylene blue and tetracycline. The theoretical maximum adsorption capacity of the composite membrane for methylene blue is 297.96 mg / g, and the theoretical maximum adsorption capacity for tetracycline is 314.38 mg / g. Compared with the pure BC membrane, the adsorption performance of the composite membrane is improved by orders of magnitude, which is attributed to the synergistic effect of the high specific surface area of NH2-MIL-101(Fe), abundant amino active sites, and the three-dimensional network structure of BC. Furthermore, after five cycles of use, the removal rate of methylene blue and tetracycline by the composite membrane obtained in this invention can still be maintained above 85%, indicating that it has good reusability and structural stability, and has practical application potential.
[0026] (4) The preparation method of the present invention is mainly carried out in four steps. The required equipment mainly includes a homogenizer, a stainless steel high-pressure reactor, a vacuum filtration device, a vacuum drying oven or a freeze dryer. The reaction temperature is up to 150°C. The method is simple, the conditions are mild, the preparation process is environmentally friendly, and there is no need for complex and expensive equipment, so the cost is low.
[0027] (5) The composite membrane prepared by the present invention has a complete membrane structure, good flexibility, and is easy to be taken out of the water body as a whole for recycling and reuse. It solves the problems of difficult separation and recycling of powder MOFs and short service life. It can be used for the deep treatment of pharmaceutical wastewater, dyeing and printing wastewater and antibiotic-polluted water bodies, and has good industrial application prospects.
[0028] The present invention will be explained in detail below with reference to the accompanying drawings and specific embodiments. Attached Figure Description
[0029] Figure 1 The images show a comparison of scanning electron microscope (SEM) images of MIL-101(Fe) and NH2-MIL-101(Fe) prepared in Example 1 of this invention; where (A) is MIL-101(Fe), which has a regular octahedral structure; and (B) is NH2-MIL-101(Fe), which has polyhedral prisms and pyramidal particles. Figure 2 Digital photographs of the NH2-MIL-101(Fe) / TEMPO-BC composite membrane prepared in Example 3; where (A) is the dried NH2-MIL-101(Fe) / TEMPO-BC-2 composite membrane, and (B) is the freeze-dried NH2-MIL-101(Fe) / TEMPO-BC-2 composite membrane; Figure 3The images show the SEM surface morphology of the NH2-MIL-101(Fe) / TEMPO-BC composite membranes prepared in Examples 3 and 4 of this invention; wherein (A) is NH2-MIL-101(Fe) / TEMPO-BC-1 (dried), (B) is NH2-MIL-101(Fe) / TEMPO-BC-1 (lyophilized), (C) is NH2-MIL-101(Fe) / TEMPO-BC-2 (dried), and (D) is NH2-MIL-101(Fe) / TEMPO-BC-2 (lyophilized). Figure 4 The images show the SEM morphology of the composite membranes when the amount of precursor used in the comparative examples of this invention is too small / too large; where (A) indicates that the amount of precursor used is too small, and the MOF particles are sparsely and unevenly distributed; and (B) indicates that the amount of precursor used is too large, and the MOF particles densely cover the BC fiber network. Figure 5 The N2 adsorption-desorption isotherm and pore size distribution of the NH2-MIL-101(Fe) / TEMPO-BC composite membrane prepared in Example 3 of this invention are shown below. Figure 6 The images show the Fourier Transform Infrared (FTIR) and XPS full spectrum of the NH2-MIL-101(Fe) / TEMPO-BC composite film prepared in Example 3 of this invention; where (A) is the FTIR spectrum and (B) is the XPS full spectrum. Figure 7 This is a fitted diagram of the adsorption isotherms of methylene blue (MB) and tetracycline (TC) on the NH2-MIL-101(Fe) / TEMPO-BC composite membrane prepared in Example 3 of the present invention.
[0030] Figure 8 The graph shows the adsorption and recycling performance of the NH2-MIL-101(Fe) / TEMPO-BC composite membrane prepared in Example 3 of this invention for methylene blue (MB) and tetracycline (TC). Detailed Implementation
[0031] To facilitate understanding of the present invention, a more comprehensive description of the present invention will be given below with reference to the accompanying drawings, which illustrate several embodiments of the present invention. However, the present invention can be implemented in different forms and is not limited to the embodiments described in the text. Rather, these embodiments are provided to make the disclosure of the present invention more thorough and comprehensive.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0033] Example 1: Synthesis of NH2-MIL-101(Fe) powder This embodiment is used to compare and verify the morphological differences between NH2-MIL-101(Fe) and unaminated MIL-101(Fe), and to provide NH2-MIL-101(Fe) samples under different synthesis conditions for subsequent composite membrane preparation.
[0034] Method 1: Weigh 0.6622 g (2.45 mmol) FeCl3·6H2O and 0.2246 g (1.24 mmol) 2-aminoterephthalic acid and dissolve them in 30 mL of LDM. After ultrasonic mixing for 30 min, transfer the mixture to a 50 mL stainless steel high-pressure reactor and place it in an oven at 110 °C for 20 h. After the reaction is complete, cool to room temperature. Wash the crude product by centrifugation with ethanol (8000 r / min, 10 min), repeating 3 times; then activate it with hot ethanol (60 °C, 3 h), repeating 2 times. Filter the product, dry it in a vacuum drying oven at 70 °C for 30 min, and then dry it at 150 °C for 8 h to obtain NH2-MIL-101(Fe).
[0035] Method 2: Weigh 1.35g FeCl3·6H2O and 0.45g 2-aminoterephthalic acid, and dissolve them in 30mL DMF. After ultrasonic mixing for 30min, transfer the mixture to a 50mL stainless steel high-pressure reactor, place it in an oven, and react at 110℃ for 24h. After the reaction is complete, cool to room temperature, and wash the crude product by centrifugation (18000r / min, 10min) three times; then wash twice alternately with DMF and ethanol. Dry in a vacuum drying oven at 70℃ overnight to obtain NH2-MIL-101(Fe).
[0036] Synthesis of MIL-101(Fe) (Control): Weigh 0.6622 g (2.45 mmol) FeCl3·6H2O and 0.2060 g (1.24 mmol) terephthalic acid, and dissolve them in 30 mL of LDMF. Subsequent steps were identical to those of NH2-MIL-101(Fe) Method 1, yielding MIL-101(Fe).
[0037] Characterization results: such as Figure 1As shown in the SEM images, MIL-101(Fe) exhibits a regular octahedral structure with smooth particle surfaces and uniform size. NH2-MIL-101(Fe) displays polyhedral prisms and pyramidal particles, along with some dispersed fragments. The SEM morphologies of NH2-MIL-101(Fe) and MIL-101(Fe) are generally similar, both being octahedral or variants, but NH2 functionalization results in a slightly rougher surface morphology and localized structural differences. This rough surface morphology is beneficial for increasing the specific surface area and active sites of the material.
[0038] Example 2: Preparation of TEMPO-oxidized bacterial cellulose nanofibers Buffer preparation (0.05M NaH2PO4-Na2HPO4 buffer, pH=6.0): Weigh 6g NaH2PO4 and prepare 1L of solution (solution A). Weigh 7.1g Na2HPO4 and prepare 1L of solution (solution B). Mix 192mL of solution A and 208mL of solution B thoroughly to obtain 400mL of 0.05M phosphate buffer.
[0039] TEMPO oxidation reaction: (1) Take bacterial cellulose hydrogel (equivalent to 1.0 g of oven-dried cellulose) and place it in a beaker. Add 150 mL of the above phosphate buffer and stir in a 60°C water bath for 30 min to obtain BC reaction solution. (2) Take another 150 mL of phosphate buffer and add 9.6 mL of NaClO solution. Stir evenly to obtain NaClO mixture. (3) Add 0.18 g of 4-acetamido-TEMPO, the NaClO mixture prepared in step (2), and 12 g of NaClO2 to the BC reaction solution in sequence. Stir and react in a 60°C water bath for 24 h. (4) After the reaction is completed, add 15 mL of ethanol to terminate the reaction. (5) Wash the BC hydrogel after TEMPO oxidation with a large amount of deionized water until neutral, and then centrifuge and wash with water (10000 r / min, 15 min). Repeat 3 times.
[0040] Homogenization: The TEMPO-oxidized BC hydrogel (after washing) was homogenized using an ultra-high-speed universal homogenizer. Specifically, the homogenizer was first homogenized at 8000 rpm for 5 min, and then repeated twice; then homogenized at 10000 rpm for 5 min, and then repeated twice, to obtain a TEMPO-oxidized bacterial cellulose nanofiber suspension.
[0041] Example 3: Preparation of NH2-MIL-101(Fe) / TEMPO-BC composite membrane The TEMPO-oxidizing bacterial cellulose nanofiber suspension prepared in Example 2 (equivalent to 1.0 g of oven-dried cellulose) was added to a DMF (60 mL) solution containing FeCl3·6H2O (1.35 g) and 2-aminoterephthalic acid (0.45 g), and then transferred to a 200 mL stainless steel high-pressure reactor and reacted at 110 °C for 24 h.
[0042] After the reaction is completed and cooled to room temperature, the following post-treatment is performed: (1) Wash with ethanol by centrifugation (8000 r / min, 10 min), repeat 3 times; (2) Activate with hot ethanol (60℃, 3 h), once; (3) Wash with deionized water by centrifugation (8000 r / min, 10 min), repeat 3 times.
[0043] The washed composite material was crushed into a uniform slurry using a crusher, and then vacuum filtered to form a membrane. The composite membrane obtained by vacuum filtration was subjected to two drying treatments: (1) Vacuum oven drying: The composite membrane was placed in a vacuum drying oven and dried at 60°C for 24 hours, denoted as NH2-MIL-101(Fe) / TEMPO-BC-2 (drying). (2) Freeze-drying: The composite membrane was placed in a -20°C freezer for 12 hours and then transferred to a freeze dryer for 24 hours, denoted as NH2-MIL-101(Fe) / TEMPO-BC-2 (freeze-drying).
[0044] Physical observation of samples: such as Figure 2 As shown, the membranes prepared by the two drying methods have similar macroscopic appearances, but there are obvious differences. Figure 2 A is the dried NH2-MIL-101(Fe) / TEMPO-BC-2 composite membrane. The dried sample is brittle, easily broken, and has a slightly rough surface. Figure 2 B is a freeze-dried NH2-MIL-101(Fe) / TEMPO-BC-2 composite membrane. The freeze-dried sample has a smooth surface and good flexibility, making it less prone to breakage and easier to operate and apply in practice.
[0045] SEM images of the membranes prepared by the two drying methods are shown below. Figure 3 As shown in (C) and (D).
[0046] Example 4: Comparative Experiment of Different Synthesis Methods and Drying Methods To further compare the effects of different synthesis methods and drying methods on the composite membrane structure, a control sample was also prepared using the conditions of method one in Example 1.
[0047] The specific operation was as follows: The TEMPO-oxidizing bacterial cellulose nanofiber suspension prepared in Example 2 (equivalent to 1.0 g of oven-dried cellulose) was added to a 30 mL DMF solution containing FeCl3·6H2O (0.6622 g) and 2-aminoterephthalic acid (0.2246 g), and transferred to a 50 mL stainless steel high-pressure reactor. The reaction was carried out at 110 °C for 20 h. Subsequent post-treatment and film formation steps were the same as in Example 3. The following results were obtained: NH2-MIL-101(Fe) / TEMPO-BC-1 (dried), dried in a vacuum oven (60 °C, 24 h); and NH2-MIL-101(Fe) / TEMPO-BC-1 (lyophilized), lyophilized.
[0048] SEM images of the membranes prepared by the two drying methods are shown below. Figure 3 As shown in (A) and (B).
[0049] Example 5: This example uses the same total amount of formula as Example 3, only adjusting the volume ratio of suspension to precursor solution.
[0050] The specific procedure is as follows: Take the TEMPO-oxidizing bacterial cellulose nanofiber suspension prepared in Example 2 (take the amount equivalent to 1.0 g of oven-dried cellulose and concentrate it to about 30 mL) and add it to a DMF solution containing FeCl3·6H2O (1.35 g) and 2-aminoterephthalic acid (0.45 g) (i.e., one-quarter of the volume of the precursor solution in Example 3), so that the volume ratio of the suspension to the precursor solution is about 2:1. Transfer it to a 100 mL stainless steel high-pressure reactor and react at 110 °C for 24 h.
[0051] The subsequent post-processing steps, including washing, vacuum filtration for membrane formation, and freeze-drying, were exactly the same as in Example 3. The resulting composite membrane was labeled NH2-MIL-101(Fe) / TEMPO-BC-3 (lyophilized).
[0052] Characterization results showed that the NH2-MIL-101(Fe) particles in the composite membrane were still uniformly distributed along the BC fiber network. However, due to the reduced volume and increased concentration of the precursor solution, the nucleation density of the MOF crystals was slightly lower, and the particle size was slightly larger than in Example 3, with a relatively sparse distribution, but no significant aggregation was observed. The three-dimensional porous network structure of BC was well preserved. The BET specific surface area was 105.4 m². 2The / g indicates that although the MOF loading is lower than that at a volume ratio of 1:2, the composite membrane still maintains a high specific surface area and a complete pore structure. Adsorption experiments show that the composite membrane still has good adsorption performance for methylene blue and tetracycline, with a removal rate maintained above 80% after 5 cycles. The above results demonstrate that effective loading of NH2-MIL-101(Fe) on BC fibers can still be achieved at a volume ratio of 2:1, proving the feasibility of the protected volume ratio range claimed in this invention.
[0053] Comparative Example 1: Insufficient Precursor Amount The amount of FeCl3·6H2O used in Example 3 was reduced to 0.45g, and the amount of 2-aminoterephthalic acid was reduced to 0.15g (i.e., reduced to one-third of the amount used in Example 3). The remaining operations were completely consistent with those in Example 3, including post-treatment washing, vacuum filtration for membrane formation, and freeze drying steps.
[0054] The results are as follows Figure 4 As shown in (A), the SEM image shows that the MOF particles in the composite film are sparsely and unevenly distributed, and some BC fiber surfaces are even without MOF particle loading, indicating that when the amount of precursor is insufficient, a continuous and uniform MOF crystal layer cannot be formed on the surface of BC fibers.
[0055] Comparative Example 2: Excessive Use of Precursor The amount of FeCl3·6H2O used in Example 3 was increased to 4.05g, and the amount of 2-aminoterephthalic acid was increased to 1.35g (i.e., increased to 3 times the amount used in Example 3). The remaining operations were completely consistent with those in Example 3, including post-treatment washing, vacuum filtration for membrane formation, and freeze drying steps.
[0056] The results are as follows Figure 4 As shown in (B), the SEM image shows that the MOF particles in the composite membrane are particularly dense, completely covering the fiber network structure of BC, which leads to the blockage of the three-dimensional porous structure of BC. This will seriously affect the mass transfer efficiency during the adsorption process and is not conducive to the rapid diffusion and adsorption of pollutants.
[0057] Performance testing and characterization 1. Morphological observation using scanning electron microscopy (SEM) The composite films prepared in Examples 3 and 4 were subjected to SEM morphology observation.
[0058] like Figure 3 As shown, Figure 3 (A) shows NH2-MIL-101(Fe) / TEMPO-BC-1 (drying). It can be seen that the overall structure of the composite membrane after drying is relatively collapsed, the MOF particles are unevenly distributed, and MOF agglomeration occurs in some areas. Figure 3(B) is NH2-MIL-101(Fe) / TEMPO-BC-1 (lyophilized). The lyophilized composite membrane has a significantly more uniform structure, and the MOF particles grow in an orderly manner along the BC veins, but there are still some areas where the MOF distribution is not dense enough. Figure 3 (C) is NH2-MIL-101(Fe) / TEMPO-BC-2 (dried), using the optimized synthesis method (method two in Example 1). Even after drying, the distribution uniformity of MOF particles is better than that of method one, but the overall network structure still collapses to some extent. Figure 3 (D) is NH2-MIL-101(Fe) / TEMPO-BC-2 (lyophilized), which is the most preferred embodiment of this invention. The three-dimensional nanonetwork provides good support for the MOF particles, which grow orderly along the BC veins, are uniformly and densely distributed, and show no significant agglomeration. Simultaneously, the three-dimensional porous network structure of BC is well preserved. The results show that the structures of NH2-MIL-101(Fe) / TEMPO-BC synthesized by the two methods differ, and the optimal microstructure can be obtained by combining method two with lyophilization.
[0059] 2. Specific Surface Area and Pore Structure Analysis (BET) The composite membranes prepared in Examples 3 and 4 were subjected to N2 adsorption-desorption tests.
[0060] like Figure 5 As shown, the N2 adsorption-desorption isotherm of the composite membrane exhibits a typical type IV isotherm, indicating the presence of a mesoporous structure. The pore size distribution is concentrated around 0.8 nm.
[0061] The specific surface area test results are as follows:
[0062] The above results indicate that the optimized synthesis method (Method 2) can significantly improve the specific surface area of the composite membrane, and freeze-drying, compared with vacuum oven drying, can better preserve the porous structure of the composite membrane, further increasing the specific surface area. The specific surface area of NH2-MIL-101(Fe) / TEMPO-BC-2 (lyophilized) is much higher than that of the pure BC membrane, providing abundant active sites and mass transfer channels for pollutant adsorption.
[0063] 3. Fourier Transform Infrared Spectroscopy (FTIR) Analysis FTIR analysis was performed on NH2-MIL-101(Fe) / TEMPO-BC-2 (lyophilized) prepared in Example 3.
[0064] like Figure 6 As shown in (A), the infrared spectrum of the composite membrane shows: 3348 cm⁻¹ -1The characteristic peak at 1651 cm⁻¹ is attributed to the stretching vibration of the hydroxyl groups in cellulose; -1 The characteristic peak at 1382 cm⁻¹ is attributed to the stretching vibration of the amide bond, indicating that a covalent bond was formed between NH₂-MIL-101(Fe) and TEMPO-oxidized BC through a chemical reaction, rather than a simple physical mixing; -1 The characteristic peak at 1257 cm⁻¹ is attributed to the stretching vibration of the CN bond, originating from the amino functional group; -1 The characteristic peak at 768 cm⁻¹ is attributed to the stretching vibration of CO in the carboxyl group; -1 The characteristic peak at [location] corresponds to the out-of-plane bending vibration of CH on the 1,2,4-substituted benzene ring. FTIR results confirm that NH2-MIL-101(Fe) was successfully covalently modified onto TEMPO-oxidizing bacterial cellulose, with strong interfacial bonding.
[0065] 4. X-ray photoelectron spectroscopy (XPS) analysis XPS analysis was performed on NH2-MIL-101(Fe) / TEMPO-BC-2 (lyophilized) prepared in Example 3.
[0066] like Figure 6 As shown in (B), the characteristic peaks of four elements, C, N, O and Fe, are clearly visible in the XPS full spectrum, which is completely consistent with the chemical composition of the composite film, further confirming the successful preparation of the NH2-MIL-101(Fe) and TEMPO-BC composite material.
[0067] 5. Adsorption isotherm experiment The NH2-MIL-101(Fe) / TEMPO-BC-2 (lyophilized) composite membrane prepared in Example 3 was subjected to adsorption isotherm testing.
[0068] Weigh 10 mg of the composite membrane and add it to 10 mL of methylene blue solution and tetracycline solution of different concentrations (10, 20, 30, 40, 50 mg / L), respectively. Shake in a constant temperature shaker at 25 °C for 12 h. After adsorption equilibrium is reached, collect the supernatant and use a UV-Vis spectrophotometer to determine the concentration of the remaining pollutants in the solution.
[0069] The experimental data were fitted using the Langmuir adsorption isotherm (Equation 1) and the Freundlich adsorption isotherm (Equation 2): Formula 1); (Equation 2); in: C e (mg / L) is the adsorption equilibrium concentration. q e (mg / g) represents the adsorption capacity at equilibrium.q m (mg / g) represents the theoretical maximum adsorption capacity. K L (L / mg) and K F (mg / g·(L / mg)^(1 / n)) represent the adsorption equilibrium constants of the Langmuir and Freundlich adsorption models, respectively. n It is a constant related to the adsorption strength.
[0070] like Figure 7 As shown, the fitting results are shown in the table below:
[0071] For methylene blue adsorption, the correlation coefficient of the Langmuir model fit. R 2 =0.9741, higher than 0.9089 for the Freundlich model, indicating that the adsorption of methylene blue by NH2-MIL-101(Fe) / TEMPO-BC is more consistent with the Langmuir model, representing monolayer adsorption, suggesting a uniform distribution of active adsorption sites on the composite membrane surface. The theoretical maximum adsorption capacity of methylene blue calculated using the Langmuir model is 297.96 mg / g.
[0072] For tetracycline adsorption, the correlation coefficient of the Freundlich model fit. R 2 =0.9960, higher than 0.9743 of the Langmuir model, indicating that the isothermal adsorption of tetracycline by NH2-MIL-101(Fe) / TEMPO-BC is closer to the Freundlich model, and the adsorption process involves intermolecular interactions of the adsorbate, which is a multilayer adsorption. The theoretical maximum adsorption capacity of tetracycline calculated by the Langmuir model is 314.38 mg / g.
[0073] Compared to the adsorption performance of pure BC, the adsorption capacity of the composite membrane is increased by orders of magnitude, thanks to the synergistic effect of the high specific surface area of NH2-MIL-101(Fe), abundant amino active sites, and the three-dimensional network structure of BC.
[0074] 6. Cyclic Use Performance Test The NH2-MIL-101(Fe) / TEMPO-BC-2 (lyophilized) composite membrane prepared in Example 3 was subjected to a recycling performance test.
[0075] The adsorption-saturated composite membrane was washed three times with alternating ethanol and deionized water, and then put into the next round of adsorption experiments. The above operation was repeated five times.
[0076] like Figure 8 As shown, after five cycles of use, the composite membrane still maintains a removal rate of over 85% for methylene blue and tetracycline, indicating that the composite membrane has good reusability and structural stability, and has potential for practical application.
[0077] In summary, the NH2-MIL-101(Fe) / bacterial cellulose composite membrane material provided by this invention possesses high adsorption performance (MB: 297.96 mg / g, TC: 314.38 mg / g), excellent reusability (removal rate >85% after 5 cycles), and good flexibility (freeze-dried sample). It is suitable for the advanced treatment of pharmaceutical wastewater, dyeing and printing wastewater, and antibiotic-contaminated water bodies. The preparation method of this invention is mild (reaction temperature 110℃), simple in steps, requires no complex and expensive equipment, and is low in cost. Furthermore, the composite membrane has a complete membrane structure, making it easy to remove and recycle as a whole from the water body, solving the problem of difficult separation and recovery of powdered MOFs. It has broad market prospects and industrial application value.
[0078] The present invention has been described by way of example in conjunction with the accompanying drawings. Obviously, the specific implementation of the present invention is not limited to the above-described manner. Any non-substantial improvement made by adopting the inventive concept and technical solution of the present invention, or the direct application of the inventive concept and technical solution of the present invention to other occasions without modification, shall be within the protection scope of the present invention.
Claims
1. A method for preparing an NH2-MIL-101(Fe) / bacterial cellulose composite membrane, characterized in that: Includes the following steps: (1) After the bacterial cellulose raw material is oxidized by the TEMPO oxidation system, it is then homogenized to obtain a TEMPO oxidized bacterial cellulose nanofiber suspension. (2) Iron salt and 2-aminoterephthalic acid were dissolved in an organic solvent to prepare a precursor solution; (3) The TEMPO-oxidized bacterial cellulose nanofiber suspension was mixed with the precursor solution and an in-situ growth reaction was carried out under hydrothermal conditions to load NH2-MIL-101(Fe) crystals on bacterial cellulose nanofibers in situ, thereby obtaining NH2-MIL-101(Fe) / bacterial cellulose composite material. (4) After washing the composite material to remove unreacted substances, it is subjected to film formation treatment and dried to obtain NH2-MIL-101(Fe) / bacterial cellulose composite membrane.
2. The method for preparing an NH2-MIL-101(Fe) / bacterial cellulose composite membrane according to claim 1, characterized in that: In step (1), the TEMPO oxidation system contains 4-acetamido-TEMPO, NaClO, and NaClO2; The oxidation treatment is carried out at a temperature of 50–70°C for 12–36 hours.
3. The method for preparing an NH2-MIL-101(Fe) / bacterial cellulose composite membrane according to claim 1, characterized in that: In step (1), the homogenization process is a gradient homogenization process, which first homogenizes at 6000-10000 rpm for 3-10 min, and then homogenizes at 8000-12000 rpm for 3-10 min.
4. The method for preparing an NH2-MIL-101(Fe) / bacterial cellulose composite membrane according to claim 1, characterized in that: In step (2), the iron salt is ferric chloride hexahydrate, and the molar ratio of the iron salt to 2-aminoterephthalic acid is 1:1 to 3:
1.
5. The method for preparing an NH2-MIL-101(Fe) / bacterial cellulose composite membrane according to claim 1, characterized in that: In step (2), the organic solvent is N,N-dimethylformamide.
6. The method for preparing an NH2-MIL-101(Fe) / bacterial cellulose composite membrane according to claim 1, characterized in that: In step (3), the volume ratio of the TEMPO oxidizing bacterial cellulose nanofiber suspension to the precursor solution is 1:2 to 2:
1.
7. The method for preparing an NH2-MIL-101(Fe) / bacterial cellulose composite membrane according to claim 1, characterized in that: In step (3), the hydrothermal reaction conditions are: reaction temperature 100-150℃, reaction time 20-30h.
8. The method for preparing an NH2-MIL-101(Fe) / bacterial cellulose composite membrane according to claim 1, characterized in that: In step (4), the washing includes: first washing with ethanol by centrifugation, then activating with hot ethanol, and finally washing with deionized water by centrifugation. The film-forming process is vacuum filtration film formation; The drying process is either vacuum oven drying or freeze drying.
9. An NH2-MIL-101(Fe) / bacterial cellulose composite membrane, characterized in that: It is prepared by the preparation method according to any one of claims 1-8.
10. The application of the NH2-MIL-101(Fe) / bacterial cellulose composite membrane according to claim 9, characterized in that: The NH2-MIL-101(Fe) / bacterial cellulose composite membrane is used to adsorb organic pollutants in water, wherein the organic pollutants are selected from at least one of organic dyes and antibiotics.